The existence of the Ahmadiyya in Indonesian democracy: a struggle for survival in the midst of the Islamic-movement competition - Usman, M.; Widodo, Aris; Aini, Shofwatul (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2022)
This article attempts to portray the competition of forces in the Indonesian democratic system, with the Ahmadiyya movement as the test case for the “contestation”. This article takes into account the reformation era as the landscape of the study, since this era opens a relatively wider opportunity for many entities to freely express their ideas and actions. Exploring the socio-political approach, this study comes up with the following findings: first, in the sociological domain, as predicted by Dawam Rahardjo, moderates defeat radical Indonesian Islam as the former outnumber the latter. However, in the political domain, as pointed out by Martin van Bruinessen, since the moderate Islam is just a silent majority, then the radical Islam wins the competition - marked by the issuance of the SKB Tiga Menteri, because the factor at work in the winning of this political competition is more on the “logic of power”, rather than the “power of logic”. The victory of the radical Islam in the political domain in turn implies at the failure of the Ahmadiyya movement in its struggle for survival in Indonesia.